Digital technologies and the oral production development in ELT: Echoing worldwide teacher’s voice - Rio, Marlon (The ESPecialist, 2020)
Oral production development has been overemphasized to be one of the hardest ones, considering the multiple hindrances coming alongside its development (OSBORN et al., 2008). Similarly, there have been some initiatives from worldwide English teachers bringing contextually meaningful solutions to solve such issues (POP et al., 2011; SONG, 2009). One of them has been vowed to be digital technologies, which would work, under a sociocultural perspective, as a potential learning and mediational tool (JOHNSON, 2009). This article, thence, displays an initial research carried out with thirty English teachers coming from thirteen countries. They were given the chance to voice their experiences regarding the use of digital technologies in developing the oral production. Preliminarily results demonstrate teachers’ will to make more often the use of digital technologies in the development of the oral production of their students, albeit many of them do not seemingly have the suitable knowledge to properly apply the learning potentialities of such digital tools. The teachers also claim to have already had both positive and negative experiences while making use of these tools, revealing the need to more fitly assist these professionals with more academic and professional support contextually applied to their realities.